SARS-CoV-2 modulates inflammatory responses of alveolar epithelial type II cells via PI3K/AKT pathway - Al-Qahtani, Ahmed A.; Pantazi, Ioanna; Alhamlan, Fatimah S.; Alothaid, Hani; Matou-Nasri, Sabine; Sourvinos, George; Vergadi, Eleni; Tsatsanis, Christos (Frontiers in Immunology, 2022)
Background SARS-CoV-2 infects through the respiratory route and triggers inflammatory response by affecting multiple cell types including type II alveolar epithelial cells. SARS-CoV-2 triggers signals via its Spike (S) protein, which have been shown to participate in the pathogenesis of COVID19. Aim Aim of the present study was to investigate the effect of SARS-CoV2 on type II alveolar epithelial cells, focusing on signals initiated by its S protein and their impact on the expression of inflammatory mediators. Results For this purpose A549 alveolar type II epithelial cells were exposed to SARS CoV2 S recombinant protein and the expression of inflammatory mediators was measured. The results showed that SARS-CoV-2 S protein decreased the expression and secretion of IL8, IL6 and TNFα, 6 hours following stimulation, while it had no effect on IFNα, CXCL5 and PAI-1 expression. We further examined whether SARS-CoV-2 S protein, when combined with TLR2 signals, which are also triggered by SARS-CoV2 and its envelope protein, exerts a different effect in type II alveolar epithelial cells. Simultaneous treatment of A549 cells with SARS-CoV-2 S protein and the TLR2 ligand PAM3csk4 decreased secretion of IL8, IL6 and TNFα, while it significantly increased IFNα, CXCL5 and PAI-1 mRNA expression. To investigate the molecular pathway through which SARS-CoV-2 S protein exerted this immunomodulatory action in alveolar epithelial cells, we measured the induction of MAPK/ERK and PI3K/AKT pathways and found that SARS-CoV-2 S protein induced the activation of the serine threonine kinase AKT. Treatment with the Akt inhibitor MK-2206, abolished the inhibitory effect of SARS-CoV-2 S protein on IL8, IL6 and TNFα expression, suggesting that SARS-CoV-2 S protein mediated its action via AKT kinases. Conclusion The findings of our study, showed that SARS-CoV-2 S protein suppressed inflammatory responses in alveolar epithelial type II cells at early stages of infection through activation of the PI3K/AKT pathway. Thus, our results suggest that at early stages SARS-CoV-2 S protein signals inhibit immune responses to the virus allowing it to propagate the infection while in combination with TLR2 signals enhances PAI-1 expression, potentially affecting the local coagulation cascade.